2011
DOI: 10.1177/1420326x11427340
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Facilities and Environmental Values on Recycling in an Office Environment

Abstract: With rising costs of landfill and waste management for businesses, it is increasingly important to understand how to gain high recycling rates through self-separation by occupants in the office environment. Through a detailed case study approach, this paper shows that the office environment does have a profound effect on environmental behaviour. The findings indicate that with careful analysis, facilities can be designed around behaviour to encourage the highest possible recycling rates. The paper shows that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Brothers et al (1994) reported that proximity of facilities (trash, containers and bins) coupled with memos over time had a significant effect on employees' recycling behavior, diminishing the cost of trash removal. Price and Pitt (2012) confirmed these findings and claimed that location of available facilities affected non-recycling activities at work more than personal attitude toward the environment.…”
Section: The Moderating Effect Of Perceived Behavioral Controlsupporting
confidence: 76%
See 2 more Smart Citations
“…Brothers et al (1994) reported that proximity of facilities (trash, containers and bins) coupled with memos over time had a significant effect on employees' recycling behavior, diminishing the cost of trash removal. Price and Pitt (2012) confirmed these findings and claimed that location of available facilities affected non-recycling activities at work more than personal attitude toward the environment.…”
Section: The Moderating Effect Of Perceived Behavioral Controlsupporting
confidence: 76%
“…As noticed Klein and Huffman (2013) although "recycling is one of the lower-impact environmental sustainability behaviors, it still provides substantial savings to organizations " (p. 8). Surprisingly, whereas most prior research has addressed individuals' recycling behavior in non-work domains (e.g., Fiorillo , 2013;Hornik, Cherian, Madansky & Narayana, 1995;Gillespie & Bennett, 2013;Schultz, Oskamp & Mainieri, 1995;Sidique, Lupi & Joshi, 2010;Tucker & Speirs, 2003), workplace recycling remains largely overlooked, with the exception of a handle of research (Austin, Hatfield, Grindle, & Bailey, 1993;Brothers, Krantz & McClannahan, 1994;Greaves, Zibarras & Stride, 2013;Lee, De Young & Marans, 1995;MacDonald, 2011;Price & Pitt, 2012;Tudor, Barr, Gilg, 2007). Typically, these prior investigations on recycling in organizational settings have to a large extent put the emphasis on facilities, and revealed that maintaining employee willingness to use appropriate bins is an important challenge for organizations (Austin et al, Ramus (2001) has found that employees are more likely to engage in environmental initiatives on the job when they perceive that their supervisor encourages new ideas, is open-minded, provides regular training to subordinates, shares critical information, rewards efforts, and shows a sense of responsibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations (and conclusions) have been made in examinations of the automotive [9,10], office [11,12] and institutional [13,14] sectors. The consensus appears to be that while many IC&I establishments implement waste management programs, insufficient planning is spent on source reduction, or diverting waste from disposal.…”
Section: Literature Reviewsupporting
confidence: 67%
“…These factors are observed to form a bridge between predicting factors and barriers to waste recycling behaviours. As identified from the reviewed studies, these factors include Awareness [70,81]; Beliefs [52,66]; Environmental benefits & values [37,47,51,69]; Feedback [52,62]; Goal Setting [33,62]; Incentives & rewards [38,44]; Prompts/information/Signage [48,[56][57][58]70]; Proximity/Convenience [34,75]; Social (subjective & descriptive) norms [40,50,[53][54][55]; Organisation commitment [34,45]; Infrastructure (availability, adequacy and appearance) [65,71]; Knowledge [48,56]; Moral obligation/norms [54,61]; Personal benefits and values [37,58], and Culture (individualism and collectivism) [55]. While most of these factors are mainly extraneous in nature, the endurance of such extrinsic factors in reinforcing recycling behaviours over a long period of time is another challenge.…”
Section: Motivating Factorsmentioning
confidence: 99%